Bacterial effector kinases and strategies to identify their target host substrates - St. Louis, Brendyn M.; Quagliato, Sydney M.; Lee, Pei-Chung (Frontiers in Microbiology, 2023)
Post-translational modifications (PTMs) are critical in regulating protein function by altering chemical characteristics of proteins. Phosphorylation is an integral PTM, catalyzed by kinases and reversibly removed by phosphatases, that modulates many cellular processes in response to stimuli in all living organisms. Consequently, bacterial pathogens have evolved to secrete effectors capable of manipulating host phosphorylation pathways as a common infection strategy. Given the importance of protein phosphorylation in infection, recent advances in sequence and structural homology search have significantly expanded the discovery of a multitude of bacterial effectors with kinase activity in pathogenic bacteria. Although challenges exist due to complexity of phosphorylation networks in host cells and transient interactions between kinases and substrates, approaches are continuously being developed and applied to identify bacterial effector kinases and their host substrates. In this review, we illustrate the importance of exploiting phosphorylation in host cells by bacterial pathogens via the action of effector kinases and how these effector kinases contribute to virulence through the manipulation of diverse host signaling pathways. We also highlight recent developments in the identification of bacterial effector kinases and a variety of techniques to characterize kinase-substrate interactions in host cells. Identification of host substrates provides new insights for regulation of host signaling during microbial infection and may serve as foundation for developing interventions to treat infection by blocking the activity of secreted effector kinases.